Decision making systems in business administration : Proceedings of the MS'12 International conference - Gil-Lafuente, Anna M.; Barcellos-Paula, Luciano; Merigo-Lindahl, Jose M; Silva-Marins, Fernando Augusto; De Azevedo-Ritto, Antonio Carlos (World Scientific proceedings series on computer engineering and information science, 2013)
This volume presents selected papers from the MS'12 International Conference, focusing on decision-making methodologies, systems thinking, computational models, and their applications in business administration, management, and industrial processes.